Export performance of tropical timber products certified by the Malaysian Timber Certification Scheme - Saadun, Norzanalia; Mohd Noor, Khamurudin; Md Sharif, Badrul Azhar; Omar, Hishamuddin; Hariz, Mohd Husni (Penerbit Universiti Malaysia Terengganu, 2019)
A study on the export performance of timber products certified under the Malaysian Timber Certification Scheme (MTCS) was conducted from 2003 to 2015. The objectives were to analyse the trend and growth of certified timber products (CTP) and to determine the factors that influenced their export using Generalised Linear Models (GLM). The annual growth of CTP export had a fluctuating trend. The compound annual growth rate (CAGR) within the study period was estimated at 31%. The average annual growth rate (AAGR) estimated using log-linear regression analysis was 22%. The primary markets for CTP export were European countries, accounting for nearly 83% of exports over the study period. The Netherlands seemed to be the main destination for almost half (40%) of the CTP. The major product was sawn timber (59%), followed by plywood (31%). GLM revealed that the export trend of CTPunder the MTCS increased with the number of Chain-of-Custody (CoC) certificate holders. More active involvement in the MTCS CoC certification scheme by industry players could promote the growth of Malaysia’s sustainable timber trade.